Preparation of anatase TiO2 nanotube arrays dominated by highly reactive facets via anodization for high photocatalytic performances. (8th September 2016) - Lee, Hyeri; Park, Tae-Hyeon; Jang, Du-Jeon
Abstract : The exposure of the reactive {001} facets has been maximized for the high photocatalytic activity of anatase TiO2 nanotube arrays. Abstract : Well-defined uniform anatase TiO2 nanotube (TNT) arrays with predominant exposure of the highly energetic {001} facets have been prepared via a two-step anodic oxidation process of Ti foil. In order to enhance the exposure degree of the {001} facets, NH4 F has been used as a capping agent during anodization and the evolution of TNT arrays has been varied by changing the duration of anodization and the concentration of NH4 F. With the increase of the first-anodization time (up to 11 h) and/or the NH4 F concentration, the crystallite sizes, crystallinity, and exposed {001} facets of prepared TNT arrays have been found to increase. The photocatalytic activity of the as-prepared TNT arrays, evaluated by monitoring the photodegradation of rhodamine B, has been found to increase in accordance with an increase in the exposure degree of the {001} facets, indicating that the highly energetic {001} facets enhance the photocatalytic activity of TNT arrays on a large scale. The {001} facets of TNT arrays have been considered to provide oxidation sites extensively, which produce active oxygen species such as ˙OH, ˙O2 −, and H2 O2 upon UV irradiation. Our results have shown that ˙OH is the predominant highly active species for the photocatalytic degradation of organic dye pollutants via TNT arrays. We consider that this study may provide a new insight into the preparation and development of advanced photocatalytic anatase TiO2 materials.